Dynamic monitoring of lymphocyte subsets at different disease stages can predict the prognosis of acute myeloid leukemia especially in complete remission status - Xunyi Jiao; Ji Zhou; Xue Liang; Jinli Zhu; Meng Xiao; Yangyang Ding; Qianshan Tao; Hao Xiao; Yingwei Li; Huiping Wang; Zhimin Zhai (Scientific Reports)
Abstract Acute myeloid leukemia (AML) lacks effective prognostic markers. While lymphocyte subsets are recognized as valuable predictive indicators in hematologic malignancies, their role in AML remains largely unexplored, particularly during different stages of AML. Our study analyzed the levels and changes of lymphocyte subsets in AML patients at newly diagnosed (ND) and first complete remission (CR) status, and explored the correlation between lymphocyte subsets and prognosis in different disease stages. Flow cytometry detected peripheral blood lymphocyte subsets in 145 ND AML patients, 125 CR AML patients, and 47 healthy controls (HCs). Dynamic testing was conducted on 28 AML patients at both ND and CR status. Our study found significant differences in lymphocyte subsets between ND, CR, and HCs, with notable changes in CD3+T, CD4+T, CD8+T, effector T (Teff), B, and natural killer (NK) cells between ND and CR status. Low frequencies of CD8+T below HCs thresholds and high regulatory T cell (Treg) frequency above HCs thresholds in the ND group, were independent risk factors for non-response to treatment. ROC curves evaluated the prognostic value of lymphocyte subsets and established cutoff values. Lymphocyte subsets in the ND group were not significantly associated with relapse or survival. Low absolute counts of CD3+T, B, and NK cells in the CR group were linked to AML relapse, and a low NK cell count was an independent predictor of overall survival (OS). Lymphocyte subsets can act as prognostic biomarkers, and their dynamic monitoring predicts treatment response, relapse, and survival in AML.